The Theology of Poems on the Lord's Supper by the Dutch Calvinist, Constantijn Huygens (1596–1687) - Joby, Christopher ca. 20./21. Jh. (Scottish journal of theology, 2012)
In this article, I provide a detailed analysis of the poems on the Lord's Supper by the Dutch statesman and man of letters, Constantijn Huygens (1596–1687). Between 1642 and 1684, he wrote eighteen poems on this subject, sixteen in Dutch and two in Latin. The type of poem varies from pithy epigrams to sonnets, through to longer poems over fifty lines in length, replete with well-conceived poetic tropes. To date, these poems have received little scholarly attention. Huygens was a lifelong member of the Reformed church and his poetry considers themes which are central to Reformed theology, such as human sin, divine grace and human gratitude. In his poetry, he recognises that he is a sinner and that it is not sufficient merely to ask for divine forgiveness, and then sin again. He acknowledges the need to intend to change his ways, but also recognises that he can only do this with divine assistance. Huygens published most of these poems and although such a public acknowledgement of sin may seem strange to us, there is a sense in which he was performing a public act of confession, to make common cause with his fellow believers, and also perhaps to encourage them to do the same. Much of the poetry considers the ontology and efficacy of the Lord's Supper. As well as exploring familiar tropes such as the sacrament as a feast and a pledge for God's promises, Huygens also asks about the very nature of the bread and wine of the sacrament. We might expect him to ascribe little or no value to the elements themselves, beyond, to use Brian Gerrish's phrase, ‘presenting what they represent’. poetry. However, at some points, the language Huygens uses to refer to the elements, such as ‘holy bread’ and ‘healing dew’, suggests something more is at stake. Some may dismiss such phrases as mere lyrical flourish, but I argue that they point to a central tension inherent within Reformed eucharistic theology between sign and signified and, furthermore, that this poetry offers us the opportunity to explore that tension. Huygens’ poems bear comparison with the best English-language religious poetry of the seventeenth century, and remind us that poetry as well as prose can offer us valuable theological insight.